Mutation at either Arg336 or Arg562 in Factor VIII Is Insufficient for Complete Resistance to Activated Protein C (APC)-mediated Inactivation: Implications for the APC Resistance Test - Amano, Kagehiro; Michnick, Donna A.; Moussalli, Micheline; Kaufman, Randal J. (Thrombosis and Haemostasis, 1998)
Activated protein C (APC)-mediated inactivation of factor VIII (FVIII) correlates with cleavage at either Arg336 and/or Arg562. To elucidate the APC cleavage requirements for inactivation of FVIII, APC cleavage site mutants in FVIII (R336I, R562K and R336I/R562K) were made by site-directed mutagenesis. Analysis of these FVIII mutants expressed in COS-1 monkey cells demonstrated the thrombin-cleaved mutant R562K was resistant to APC cleavage at residue 562 but not at Arg336 and the thrombin cleaved mutant R336I was mostly resistant to APC cleavage at residue 336, but was sensitive to APC cleavage at Arg562. The double mutant R336I/R562K was mostly resistant to cleavage at residue 336 and completely resistant to cleavage at residue 562. Thus, APC cleavage of FVIII does not require a specific order of cleavage at either residue. The functional inactivation by APC was studied using partially purified preparations of FVIII expressed in Chinese hamster ovary cells. Both single mutants were inactivated at similar rates but slower than wild-type FVIII, whereas the double mutant R336I/R562K was resistant to inactivation. The ability of a commercially available APC-resistance assay kit to detect APC resistant FVIII was tested by reconstituting FVIII deficient plasma with the APC resistant mutants. Only the R336I/R562K demonstrated a reduced APC-resistance ratio, indicating that this assay can not detect the single APC cleavage site mutant of FVIII. These results suggest that APC-mediated cleavage at either Arg336 or Arg562 partially inactivate FVIII.